Plan estratégico para la Empresa Bananera “Curitiba” - Castro Zamora, Karla Katherine (2018)
The present investigation was carried out in the banana company "CURITIBA" located in the Maculillo Precinct, Quevedo Canton, Los Ríos Province, in a tropical climate that varies between 23 and 33 ° C. whose research objective was: Formulate the Strategic Plan for the Bananera Company "CURITIBA". The Agricultural Production Unit (UPA) where the study was made, has an area of 32 hectares of banana that is mostly destined for export. It has a staff of twelve employees and permanent workers, but is hired when the productive needs require it, especially when it is harvested, always complying with labor laws and regulations. It has basic infrastructure but according to its owners, it is essential to comply with the processes that are carried out. However, internal processes, both administrative and production, must be reviewed to optimize the resources that are scarce in all agricultural areas. For this, the implementation of a strategic plan that responds to the reality of the company and with a focus is imperative. of growth, create value and give sustainability to the Agricultural Production Unit (UPA). From the interview applied to the Manager / Owner and Administrator, the workers' surveys and the observations made in the Banana Company "Curitiba" can assure that the company is at a level of risk that is around 55%, since they have coincided in most answers; therefore, we confirm that the company has not designed a technical structure in the management of all areas such as administrative, organizational and field, which is affecting the performance that affects the profitability and the generation of value to the company. Within the proposal covers the development of a strategic plan that allows the saving of resources, good development and perform in an orderly manner whose purpose is to ensure the functionality and sustainability of the company dedicated to the production of bananas, facing the adversities and allow to solve with the least impact on itself, since activity levels are not always the best.